2021
DOI: 10.1155/2021/6043846
|View full text |Cite
|
Sign up to set email alerts
|

Combined Configuration of Container Terminal Berth and Quay Crane considering Carbon Cost

Abstract: Berths and quay cranes are scarce resources in the container terminal system. If the equipment is reasonably planned, the service quality might be improved and the operation cost of the terminal would be reduced. In addition, the competition among ports is not only the competition of the terminal service quality, throughput, and scale but also the competition of low-energy consumption and low pollution. In order to reduce carbon dioxide emissions, this paper developed a multiobjective optimization model for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Li et al proposed a new mixed-integer planning model to improve the simulation of the actual situation of container terminals by considering the bidirectional simultaneous loading and unloading operation flow and the number of critical equipment constraints ( 27 ). Duan et al developed a multi-objective optimization model for the joint configuration of container terminal berths and QCs with the objective of reducing CO 2 emissions ( 28 ). The model considers carbon costs achieved specifically by reducing vessel operating costs and minimizing average vessel waiting times and departure delays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al proposed a new mixed-integer planning model to improve the simulation of the actual situation of container terminals by considering the bidirectional simultaneous loading and unloading operation flow and the number of critical equipment constraints ( 27 ). Duan et al developed a multi-objective optimization model for the joint configuration of container terminal berths and QCs with the objective of reducing CO 2 emissions ( 28 ). The model considers carbon costs achieved specifically by reducing vessel operating costs and minimizing average vessel waiting times and departure delays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers such as [20,4] have focused on the effect of increasing the vessel's time in port on the amount of quay crane fuel consumption. Junliang He [4] formulated a mixed integer programming model to minimize the total departure delay time and the cost of quay crane energy consumption in the integrated berth allocation (BAP)and quay crane assignment (QCAP) problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of experiments show how the model is more effective. Duan et al [20] proposed a multi-objective optimization mode to schedule the berth and quay crane in the container terminal. The authors suggested a multi-objective optimization model for scheduling quay crane and berth at the container terminal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the high complexity, heuristic algorithms are usually employed for solving the BACAP [26], especially for dealing with large-scale problems. Apart from the methods mentioned above, other heuristics, especially the genetic algorithm [27], have also been applied to solve BACAP. In GA, the constraint handling strategy has a great influence on the quality of the obtained near-optimal solution.…”
Section: Introductionmentioning
confidence: 99%